Analysis of Factors Related to the Choice of Long-Term Contraception (LMP) at the Motoboi Kecil Community Health Center - Novrianti Andale; Anik Purwati (International Journal of Medicine and Health, 2025)
In addition to being programmatically successful in lowering TFR and slowing population growth rates, the Long-Term Contraceptive technique (MKJP) is an affordable technique of preventing conception. This study's objective was to examine variables associated with long-term contraceptive (MKJP) selection at the Motoboi Kecil Community Health Center. The study design is cross-sectional and the research methodology is quantitative. The investigation was carried out in the workspace of the Motoboi Kecil Community Health Center. 300 women of reproductive age made up the study's population, and a straightforward random selection procedure was used to choose 45 participants. A questionnaire was used to gather the data, which were then subjected to univariate and bivariate analysis using the Chi-Square statistical test. Age and MKJP choice did not correlate, according to the data (p-value = 0.09 > 0.05). The choice of MKJP was correlated with education (p-value = 0.003 < 0.05). The choice of MKJP was correlated with occupation (p-value = 0.003 < 0.05). The choice of MKJP and the husband's support are related, with a p value of 0.004 < 0.05. Parity and MKJP selection are related, with a p value of 0.003 < 0.05. Knowledge and MKJP selection are related, with a p-value of 0.003 < 0.05.